Collectivity Dilemma of Coffee Farmers: Perspective from Weberian Sociology (Case of Nagori Sait Buttu Saribu, Pamatang Sidamanik District, Simalungun Regency, North Sumatera) - ., Rokhani; Sumarti, Titik (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTThe aims of this study was to analyze the process of the emergence of collectivity dilemma and efforts to overcome and to analyze the characteristics of farmer groups to facilitate collective action to face the export market. Collective actions with regard to the moral and cultural values are in contrast to rational actions based on individual choices. Collective action is interpreted as a voluntary action taken by the group to achieve a common goal. The discussion of the collective actions is closely related to social capital. Social capital is the factor which seriously becomes the cause and result of collective action. The linkage of the theory of collective action and social capital is the elements of social capital (trust, networks and institutions) which become the frame as well as requirements for collective action. This research is a life history study. Some studies showed that the dilemma arises when individual interests are more dominant than the interests of the group. Dilemma collectivity can be tamed by the trust between individuals in the farmer groups. Collective action in the form of the institution of farmers groups can support farmers to meet the strick requirements required by the export market. Characteristics of farmer groups which can be use to facilitate the collective actions are small number of members, the group is formed on neighborhood ties, head of the group is a farmer as well as a trader and there are some incentives to individuals that involved actively in the group.Keywords: collective action, moral, culture, social capital, export markets, dilemma collectivityABSTRAKTujuan penelitian ini adalah menganalisis proses munculnya dilemma kolektivitas dan upaya mengatasinya dalam kelembagaan kelompok tani serta menganalisis karakteristik kelompok tani untuk menfasilitasi tindakan kolektif dalam menghadapi pasar ekspor. Tindakan kolektif berkenaan dengan moral dan budaya, berbeda dengan tindakan rasional yang didasari oleh pilihan-pilihan individu. Tindakan kolektif dimaknai sebagai tindakan sukarela yang diambil oleh kelompok untuk mencapai tujuan bersama. Pembahasan mengenai tindakan kolektif erat kaitannya dengan modal sosial. Modal sosial menjadi faktor yang menjadi penyebab dan hasil tindakan kolektif. Keterkaitan teori tindakan kolektif dan modal sosial adalah unsur-unsurmodal sosial (kepercayaan, jaringan dan institusi) yang menjadi kerangka sekaligus syarat bagi tindakan kolektif. Penelitian ini merupakan studi riwayat hidup.Hasil penelitian ini menunjukkan bahwa dilemma kolektivitas petani muncul apabila kepentingan individu lebih dominan dibandingkan kepentingan kelompok. Dilema kolektivitas petani dapat “dijinakkan” dengan kepercayaaan antar individu yang tergabung dalam kelompok tani. Tindakan kolektif dalam bentuk kelembagaan kelompok tani dapat membantu petani untuk memenuhi persyaratan ketat yang diajukan oleh pasar ekspor. Karakteristik kelompok tani yang dapat menfasilitasi tindakan kolektif adalah: jumlah anggota kecil , kelompok dibentuk atas iktan ketetanggaan, ketua kelompo ksekaligus menjadi pedagang dan ada pemberian insentif pada individu yang tergabung dalam kelompok.Kata kunci: Tindakan kolektif, moral, budaya, modal sosial, pasar ekspor, dilemma kolektivitas